Risk behaviours for HIV and hepatitis infection among anabolic-androgenic steroid users - Midgley, S. J.; Heather, N.; Best, D.; Henderson, D.; McCarthy, S.; Davies, J. B. (AIDS care, 2000)
This study examined HIV and hepatitis risk behaviours among anabolic-androgenic steroid (AAS) users and controls, providing a detailed assessment of both injection and sexual practices. Fifty AAS-using and 40 non-AAS-using weight trainers completed a semi-structured interview followed by a detailed questionnaire. The 'high risk' behaviour of sharing needles and syringes was not current practice among the AAS-using sample, with only one user reporting sharing injecting equipment in the past. However, for some users it was common practice to share multi-dose vials (19%) and to divide drugs using syringes (17%). Both these practices are potential routes for HIV and hepatitis infection. Significantly more AAS users (36%) reported increases in sex drive over the last three months than did the control subjects (5%). More AAS users than controls were engaging in sex with more than one partner while infrequently using condoms. These findings support the maintenance of needle exchange schemes which are essential to continued safe injecting practices among AAS users. The elevated sexual risk behaviour of AAS users could be due to AAS's effect of increasing sex drive or to a 'risk taking' personality trait among AAS users.